A study on the reading strategies employed by law undergraduates and practicing lawyers in case reading - Ariffin, Adlina; Mohd. Asraf, Ratnawati (2015)
How do law students and lawyers read legal cases? Do they use similar strategies or does each group have some distinctive strategies? This paper illustrates a study which aims to find answers to these questions. Using the interview technique, researcher’s observation and the think-aloud protocol (TAP), this research was conducted on eight law undergraduates and two practising lawyers. The student participants were divided into two groups - four in the High-Performance Group (HPG) and four in the Low-Performance Group (LPG). The verbalisations from the TAP were analysed using the framework of reading strategies originally developed by Deegan (1995) with a slight adaptation by Christensen (2007). The findings accentuated the different as well as similar utilization of the case reading strategies by the different respondents. The research also highlighted the distinctive characteristics of strategic readers of legal cases such as the ability to employ varied reading strategies, establish context of the case, connect to previous experiences, apply strategic thinking and incorporate their knowledge of legal practice. This study has crucial implications on the curriculum development and the pedagogical aspect in the teaching of case reading in legal education particularly to the curriculum designers, material developers, ESP instructors, legal educators and law students.